"I can read, I just can't see": a disability rights-based perspective on reading by listening. Issue 7 (22nd December 2021) - Lundh, Anna
Abstract : Purpose: The aim of the paper is to create a greater understanding of how people who are blind or vision impaired describe their use of audio-based reading technologies, with a particular focus on how they reason about whether the use of these technologies can be understood in terms of reading. Design/methodology/approach: The study is part of the emerging research area Critical Studies of Reading and draws theoretical inspiration from Document Theory, New Literacy Studies and Critical Disability Studies. The article presents a discourse analysis of how 16 university students in Australia who are blind or vision impaired and use audio-based reading technologies describe this use in semi-structured interviews. Findings: The participants relate to a division between 'real' reading and reading by listening, where the latter is constructed as an exception and is connected to the subject position of being blind or vision impaired. However, resistance is also noticeable, where reading by listening is constructed as something that is normal, and as a right. Originality/value: The article is a theoretical and empirical contribution to the ongoing discussion on the use of audio-based reading technologies. It presents perspectives from the users of these technologies and argues why a specific understanding of this use is important.